Comparative outcomes of autologous and implant-based breast reconstruction techniques: evidenced-based perspectives - Gómez, Santiago González; Méndez Pérez, Alan Amado; Guzman-Brito, Karla Paola; Saucedo Resendiz, Emmanuel Alejandro; Contreras, Rafael Chávez; Páez Arteaga, María Fernanda (International Surgery Journal, 2025)
Breast reconstruction techniques differ widely in their utilization of tissue, associated donor site morbidity, complication profiles, and patient-reported outcomes. Autologous options, such as the deep inferior epigastric perforator (DIEP) and transverse rectus abdominis myocutaneous (TRAM) flaps, are preferred for their superior long-term satisfaction, better aesthetic results, and lower complication rates, particularly in patients who have received radiotherapy. While implant-based reconstruction offers a less invasive and faster recovery alternative, it is associated with higher long-term complication rates and lower patient satisfaction. The choice of technique should consider individual patient factors, oncologic safety, and personal preferences, as the long-term quality of life and satisfaction are more closely linked to the reconstructive method than to the timing of surgery. Overall, autologous reconstructions tend to provide more durable, satisfying outcomes, emphasizing their role in personalized breast cancer care.